Association Mapping of Main Tomato Fruit Sugars and Organic Acids - Zhao, Jiantao; Xu, Yao; Ding, Qin; Huang, Xinli; Zhang, Yating; Zou, Zhirong; Li, Mingjun; Cui, Lu; Zhang, Jing (Frontiers in Plant Science, 2016)
Association mapping has been widely used to map the significant associated loci responsible for natural variation in complex traits and are valuable for crop improvement. Sugars and organic acids are the most important metabolites in tomato fruits. We used a collection of 174 tomato accessions composed of S. lycopersicum (123 accessions) and S. lycopersicum var cerasiforme (51 accessions) to detect significantly associated loci controlling the variation of main sugars and organic acids. The accessions were genotyped with 182 SSRs spreading over the tomato genome. Association mapping was conducted on the main sugars and organic acids detected by gas chromatography-mass spectrometer (GC-MS) over two years using the mixed linear model (MLM). We detected a total of 58 significantly associated loci (P<0.001) for the 17 sugars and organic acids, including fructose, glucose, sucrose, citric acid, malic acid. These results not only co-localized with several reported QTLs, including fru9.1/PV, suc9.1/PV, ca2.1/HS, ca3.1/PV, ca4.1/PV and ca8.1/PV, but also provided a list of candidate significantly associated loci to be functionally validated. These significantly associated loci could be used for deciphering the genetic architecture of tomato fruit sugars and organic acids and for tomato quality breeding.